A deletion mutation within the goat AKAP13 gene is significantly associated with litter size. Issue 2 (3rd April 2023) - Zhang, Xinwei; Yuan, Rongrong; Bai, Yangyang; Yang, Yuta; Song, Xiaoyue; Lan, Xianyong; Pan, Chuanying
Abstract: A-kinase anchoring protein 13 (AKAP13) is one of the AKAP protein family members, which is correlated with estrogen receptors (ERs) and progesterone receptor (PR) activity. Consequently, the AKAP13 gene is considered to be one of the candidate genes for regulating female fertility. Hence, the objectives of this study were to discover the potential insertion/deletion (indel) variants within the AKAP13 gene and evaluate their associations with litter size of Shaanbei white cashmere goats (SBWC) to screen candidate genes for the molecular marker-assisted selection (MAS). Ultimately, we found the 16-bp deletion of AKAP13 gene which displayed three genotypes (II, ID and DD). However, it was not confirmed to Hardy-Weinberg equilibrium (HWE) in the tested population. Statistical analysis demonstrated that this 16-bp indel locus was significantly associated with litter size in goats ( p  < 0.05), in which the ID genotype was a key genotype for increasing litter size in goats. Besides, independent χ 2 tests between different genotypes and litter size showed that high-prolific groups had higher frequency of the 'D' allele ( p  < 0.05). Briefly, AKAP13 gene is a candidate gene for improving fertility, and its 16-bp indel locus can be used as a valid DNA molecular marker for the MAS in goat breeding.